2016
DOI: 10.1021/acs.est.5b06069
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic as a Vector for Chemicals in the Aquatic Environment: Critical Review and Model-Supported Reinterpretation of Empirical Studies

Abstract: The hypothesis that 'microplastic will transfer hazardous hydrophobic organic chemicals (HOC) to marine animals' has been central to the perceived hazard and risk of plastic in the marine environment. The hypothesis is often cited and has gained momentum, turning it into paradigm status. We provide a critical evaluation of the scientific literature regarding this hypothesis. Using new calculations based on published studies, we explain the sometimes contrasting views and unify them in one interpretive framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
609
2
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,153 publications
(672 citation statements)
references
References 82 publications
13
609
2
13
Order By: Relevance
“…At this moment, several researchers suggest that this route for POP exposure to biota is minor when compared to other sources of environmental pollutants (e.g. Lohmann, 2017;Koelmans et al, 2016). Therefore, this aspect is not focused on in great deal within this report.…”
Section: Effects Of Ingestion On Fish and Invertebrates From Laboratomentioning
confidence: 98%
See 1 more Smart Citation
“…At this moment, several researchers suggest that this route for POP exposure to biota is minor when compared to other sources of environmental pollutants (e.g. Lohmann, 2017;Koelmans et al, 2016). Therefore, this aspect is not focused on in great deal within this report.…”
Section: Effects Of Ingestion On Fish and Invertebrates From Laboratomentioning
confidence: 98%
“…Most expert reviews agree that most plastic contaminated fish pose negligible risk to human health regarding PBT substances, as the plastic typically resides in the intestines, rather than muscle flesh, but there are uncertainties about the effects of nanosized plastics, which could potentially be able to translocate between (e.g. Brennecke et al, 2015b;EFSA, 2016;Koelmans et al, 2016;Lohmann 2017). However, it is also found microplastic contamination in food that are consumed directly/whole such as shellfish, table salt and honey (and many others may follow with increased research and monitoring).…”
Section: Uptake Of Microplastics Into Humans From Foodmentioning
confidence: 99%
“…Some studies of microplastic ingestion have shown that complete egestion follows, as in the marine isopod Idotea emarginata [55], or ingestion of non-buoyant microplastics by the mud snail Potampoyrgus antipodarum, which showed no deleterious effects in development during the entire larval stage [56]. A recent review concluded that hydrophobic chemicals bioaccumulated from natural prey overwhelm the flux from ingested microplastic for most habitats, implying that microplastic in the environment is not likely to increase exposure [57].…”
Section: Global Distribution Of Microplasticsmentioning
confidence: 99%
“…Plastics gradually break down to microscopically small particles, but these may pose an even more serious problem (Thompson et al 2004;Bergmann et al 2015). Although experimental results and model predictions are not all in agreement, concerns about microplastics are increasing as plastics can adsorb and concentrate organic pollutants from the surrounding water and, once ingested, might release chemicals into marine organisms with associated negative effects (Arthur et al 2009;Browne et al 2008Browne et al , 2013Endo et al 2005Endo et al , 2013Gouin et al 2011;Koelmans et al 2013aKoelmans et al ,b, 2014Koelmans et al , 2016Moore 2008;Teuten et al 2007Teuten et al , 2009Chua et al 2014;Rochman et al 2013Rochman et al , 2014aTanaka et al 2013;Thompson et al 2009;Van Cauwenberghe & Janssen 2014;Cole et al 2015;Watts et al 2015;CBD 2016;Beaman & Bergeron 2016;Peda et al 2016;Besseling et al 2017;Heindler et al 2017;Hermabessiere et al 2017;Ribeiro et al 2017). Thus, in addition to the toxic substances incorporated into plastics in the manufacturing process, plastics may concentrate pollutants from the environment and act as a pathway adding to their accumulation in marine organisms.…”
Section: Figure IV Comparative Trendsmentioning
confidence: 99%